BURNOUT OF PRIMARY AND SENIOR SECONDARY PHYSICAL EDUCATION TEACHERS IN RELATION TO THEIR LEVEL OF ASPIRATION - Dr. Suresh Kumar; Navdeep Kaur (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
The purpose of the study was to compare the burnout of primary and senior secondary Physical Education teachers in relation to their level of aspiration.  A total of 90 samples were selected from the three districts of Amritsar, Jalandhar, and Patiala of Punjab State. These samples were further divided into two groups of Physical Education teachers at the Primary and Senior Secondary levels. Each group had an equal size of 45 Samples. These subjects had a minimum of three years of teaching experience. Burnout among Physical Education teachers was measured by a questionnaire of Maslach Burnout Inventory by Maslach and Jackson (1986), whereas the level of aspiration was measured by the questionnaire of Dr. Mahesh Bhargava and Late prof. M. A. Shah (1996) for the collection of data. For the purpose of data collection of burnout of primary and senior secondary Physical Education teachers in relation to their level of aspiration was applied. To know the statistical difference t-test and Product movement correlation have been employed. The results of the present study found, a significant difference in Burnout between primary and secondary physical education teachers in relation to their professional qualification and an insignificant difference in the Level of aspiration among physical education teachers and relation to their professional qualification. In the relationship between burnout and level of aspiration among physical education teachers and in relation to their professional qualifications was a positive relationship found.